EXTRACT FROM BUTTERFLY PEA FLOWERS (Clitoria ternatea L.) AS A NATURAL INDICATOR OF ACIDS AND BASES: AN INVESTIGATIVE PROPOSAL FOR SCIENCE TEACHING (REMUNOM, 2025)
Teaching inorganic functions (acids and bases) can be a challenging task, since it is a complex topic with a large amount of information to be contextualized by students. Thus, with the aim of making teaching easier and more stimulating, this article is a didactic proposal, using the inflorescences of the species Butterfly Bean or Blue Fairy (Clitoria ternatea L.), as a natural aqueous extract as an acid-base indicator in Chemistry classes. In addition to being an experimental proposal with potential for application in the classroom, the work also reinforces the effectiveness of Butterfly Bean flowers as another viable alternative for a natural pH indicator, with great potential for distinguishing acids and bases. Using simple and accessible materials, a pH scale was constructed using everyday household products, where the natural indicator of Butterfly Bean flowers was tested. As the main result of this didactic proposal, a significant variation in the color of the natural indicator was observed in acidic products tested, such as hydrochloric acid (HCl, pH = 1), exhibiting an intense red coloration, neutral character (pH = 7) of filtered water with a blue coloration and the basic character, as was the case of sodium hydroxide (NaOH, pH = 14), with a yellow coloration. The aforementioned natural indicator, in addition to being safe and non-toxic, does not cause skin irritation and is affordable, and can be easily found in health food stores. In conclusion, the methodological proposal presented in this work has an innovative character by proposing the use of the inflorescences of this species as a natural pH indicator, opening the possibility for alternative use in experimental Chemistry classes on topics of inorganic functions, both aimed at middle and higher education levels, in addition to stimulating students' interest and facilitating the understanding of the concepts in the proposed theme.